IMPLEMENTASI UNDANG-UNDANG KEPARIWISATAAN DALAM PEMBENTUKAN BADAN PROMOSI PARIWISATA DAERAH DI PROVINSI BALI - Ni Ketut Bagiastuti (Politeknik Negeri Bali, 2013)
The rapid development of tourism in Bali is inseparable from the role of tourism organization . In Bali it has been formed basically tourism promotion agency established before the issuance of Law no.10 of 2009 concerning tourism, known as the Bali Tourism Board (Bali Tourism Board/BTB). Bali Tourism Board (Bali Tourism Board/BTB) was founded on March 1, 2000 by 9 associations. Governor of Bali, on May 10, 2000, Bali Tourism Board (Bali Tourism Board/BTB) defined as a form of partnership between the tourism industry, governments and local communities and members expanded to include the Department of Tourism, enterprises, private companies, educational institutions, associations other business-related and relevant communities. Where one of the government's mission is to carry out the task of which is to promote, build and manage Bali as a leading tourist destination. Basically the task between Bali Provincial Tourism Office, Tourism Promotion Board and Tourism Board area Bali (Bali Tourism Board/BTB) have a common task. However, the formation of the Bali Tourism Board (Bali Tourism Board/BTB) is not based on Law no.10 of 2009, so it needs to be studied further whether the Bali Tourism Board (Bali Tourism Board/BTB) is intended by the Law no.10 of 2009 on Tourism as a Regional Tourism Promotion Board or the Bali Provincial Government will establish more other Regional Tourism Promotion Board as the mandate of the Law.10 Year 2009 on Tourism.